2012
DOI: 10.2147/nsa.s23932
|View full text |Cite
|
Sign up to set email alerts
|

A review of mammalian toxicity of ZnO nanoparticles

Abstract: This review summarizes the literature on mammalian toxicity of ZnO nanoparticles (NPs) published between 2009 and 2011. The toxic effects of ZnO NPs are due to the compound's solubility. Whether the increased intracellular [Zn 2+ ] is due to the NPs being taken up by cells or to NP dissolution in medium is still unclear. In vivo airway exposure poses an important hazard. Inhalation or instillation of the NPs results in lung inflammation and systemic toxicity. Reactive oxygen species (ROS) generation likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
257
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(268 citation statements)
references
References 75 publications
11
257
0
Order By: Relevance
“…Here, addition of ZnONPs with the largest size (57 nm) to CuNPs caused the highest cytotoxicity in HepG2 cells. These findings are in agreement with the idea that the interaction of large ZnONPs aggregates with the membrane is one of the factors driving toxicity (Vakurov et al, 2013;Vandebriel and De Jong, 2012). Moreover, they indicate that the exposure of cells to combinations of NPs introduces new factors that greatly contribute to determining the global toxicity of the mixture.…”
Section: Discussionsupporting
confidence: 90%
“…Here, addition of ZnONPs with the largest size (57 nm) to CuNPs caused the highest cytotoxicity in HepG2 cells. These findings are in agreement with the idea that the interaction of large ZnONPs aggregates with the membrane is one of the factors driving toxicity (Vakurov et al, 2013;Vandebriel and De Jong, 2012). Moreover, they indicate that the exposure of cells to combinations of NPs introduces new factors that greatly contribute to determining the global toxicity of the mixture.…”
Section: Discussionsupporting
confidence: 90%
“…Although the antioxidantrelated proteins that reported by Fukui et al (including lipid peroxide, heme oxygenase-1 and alpha-tocopherol) 8) were not identi ed in our study, the other similar antioxidant proteins, peroxiredoxin-6 and -1, were observed with up-regulation in BALF of ZnO NPs exposed rats (Table 1). According to the above observations, these ndings support those reported previously, 1,6) namely that inhalation or instillation of ZnO NPs predominantly results in lung in ammation and systemic toxicity.…”
Section: Resultssupporting
confidence: 91%
“…1) As a result of all these uses, it is therefore necessary to provide a complete understanding of ZnO NPs toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO NPs are widely used in several applications including cosmetics, plastic, paints, as drug carriers, UV-stabilizer, environ mental remediat ion, wastewater treatment and fillings in medical materials (Dufour, Ku maravel, Nohynek, Kirkland, & Toutain, 2006;Vandebriel & De Jong, 2012). For Eu rope and the U.S., total concentrations of ZnO NPs in surface waters were reported as 0.010 (0.008-0.055) µg/l and 0.001 (0.001-0.003) µg/l, respectively (Gottschalk, Sonderer, Scholz, & Nowack, 2009).…”
Section: Introductionmentioning
confidence: 99%